A Viral Platform for Chemical Modification and Multivalent Display - Peabody David S (Journal of Nanobiotechnology, 2003)
Abstract The ability to chemically modify the surfaces of viruses and virus-like particles makes it possible to confer properties that make them potentially useful in biotechnology, nanotechnology and molecular electronics applications. RNA phages (e.g. MS2) have characteristics that make them suitable scaffolds to which a variety of substances could be chemically attached in definite geometric patterns. To provide for specific chemical modification of MS2's outer surface, cysteine residues were substituted for several amino acids present on the surface of the wild-type virus particle. Some substitutions resulted in coat protein folding or stability defects, but one allowed the production of an otherwise normal virus-like particle with an accessible sulfhydryl on its surface.